Efektivitas Media Index Card Match Terhadap Tingkat Pengetahuan, Sikap dan Perilaku Menstrual Hygiene - Ananda, Rahma; -, Suparmi; Widiastuti, Dhias (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2023)
Based on data from the Ministry of Health of the Republic of Indonesia in 2017, there were 5.2 million young women experiencing complaints after menstruation because they did not maintain cleanliness during menstruation, such as pruritus vulvae which is characterized by an itchy sensation on the genitals who have less knowledge about menstrual hygiene. Therefore, it is necessary to provide health education about menstrual hygiene to increase the knowledge, attitudes and behavior of young women. This study aims to determine the effectiveness of health education using index card match media on the level of knowledge, attitudes, and behavior of menstrual hygiene in young women. This type of research is a pre-experimental study with a one group pretest-posttest design. The sampling technique used a total sampling of 33 respondents. All samples were given intervention using index card match media by playing index card match twice. The research results show an increase in knowledge, attitudes,and the behavior of youngÂ women after being given health education using media index card match regarding menstrual hygiene with Wilcoxon test results each p-value 0.000 (<0.05) for the level of knowledge, attitudes and behavior. It is hoped that the results of this research can add to thisknowledge of young women about menstrual hygiene and young women canapply the knowledge about menstrual hygiene that has been acquired tochange attitudes and behavior in order to adopt a healthy life.